Abstracts 2021
DOI: 10.1136/archdischild-2021-europaediatrics.114
|View full text |Cite
|
Sign up to set email alerts
|

114 Hypothermia is preventable

Abstract: Subsequent follow-up (during the first year of life) showed that in children of the main group were less frequently detected functional disorders of the gastrointestinal tract (15.8% vs 36.5%, P=0.034) and allergic diseases (1.2% vs 5.8%, P=0.056).In newborns whose mothers received a probiotic during the 6 weeks before delivery, after birth levels of both markers of intestinal inflammation (fecal eosinophil-derived protein and fecal calprotectin) were significantly lower than in comparison group (children whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The results of the L test after treatment showed that there were no significant differences between the various groups in the measurement so that it could be said that environmental conditions affected the condition of the newborn baby rabbits. Heat dissipation due to continuous exposure to cold affected the body‘s ability to produce heat, resulting in hypothermia ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the L test after treatment showed that there were no significant differences between the various groups in the measurement so that it could be said that environmental conditions affected the condition of the newborn baby rabbits. Heat dissipation due to continuous exposure to cold affected the body‘s ability to produce heat, resulting in hypothermia ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%